Demystifying the autistic experience : a humanistic introduction for parents, caregivers, and educators - Stillman, William, 1963- (Jessica Kingsley Publishers, 2003)
Parents, caregivers and educators are often at a loss about how best to support an individual with autism because they are overwhelmed by 'behaviors', inundated with prognoses and clinical jargon, or confused by technical information. This book introduces autism from a non-clinical, humanist perspective, emphasizing that we are all more alike than different. The author deconstructs the fundamental concepts of the autistic experience using language, examples and anecdotes that are concrete and understandable for all. Reinforced for the reader is the importance of listening carefully to what peo.